Displacement Based Earthquake Early Warning Systems - Murat Doruk Şentürk; Bahadır Aktuğ (Doğal Afetler ve Çevre Dergisi)
Displacement based earthquake observations are becoming more common and application fields are becoming larger. The determination of the earthquake magnitude in a short time after the earthquake plays an important role both for Earthquake Early Warning Systems (EEW) and the estimation of the losses and coordinating the rescue efforts. However, magnitude estimation from the displacement waveforms for the 1999 Chi-Chi (Mw7.6), 1999 Hector Mine (Mw7.1) and 2003 Tokachi-Oki (Mw8.3) earthquake shows that while they are more precise, the earthquake magnitudes were underestimated (Brown et al. 2011; Crowell et al. 2013). There are well known bottlenecks with the velocity measuring seismometers due to the fact that they get saturated nearby large earthquakes or they do not provide sufficient time for early warning when they are away from the earthquake source. Geodetic measurements and accelerometer records provide data from the close vicinity of the earthquake source and enable to determine to static offsets and the earthquake magnitude based on displacements since GNSS receivers operate in a non-inertial reference frame. Nowadays, earthquake early warning systems based on seismogeodetic observations are being established and becoming more common in countries subject to earthquake hazard such as USA and Japan. In this study, earthquake magnitudes were estimated for several recent earthquakes in Turkey only by using the GNSS displacement waveforms. GNSS_based Re-estimation of the earthquake magnitudes for Gökova, Gökçeada and Van earthquakes resulted in the magnitudes of 6.54, 7.21 ve and 7.22 Mw, respectively, corresponding to the original magnitudes of 6.6, 6.9, 7.2. These results show that earthquake magnitudes based on GNSS waveforms provide high precision and their potential for use in earthquake early warning.